Nomenklatorische Bemerkungen zu palaearktischen Acrolepiiden (Lepidoptera). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1979)
Three new synonymies among the palearctic Acrolepiidae were found and are substantiated: Swammerdamia maculatella Turati, 1930 = Digitivalva eglanteriella (Mann, 1855), Acrolepiopsis persimilis Moriuti, 1974 = Acrolepiopsis suzukiella (Matsumura, 1931) and Acrolepiopsis sapporensis Moriuti, 1975 = Acrolepiopsis alliella (Semenov et Kuznecov, 1956). Nomenclatural Acts persimilis Moriuti, 1974 (Acrolepiopsis), syn. n. of Acrolepiopsis suzukiella (Matsumura, 1931) sapporensis Moriuti, 1975 (Acrolepiopsis), syn. n. of Acrolepiopsis alliella (Semenov & Kuznecov, 1956) maculatella Turati, 1930 (Swammerdamia), syn. n. of Digitivalva eglanteriella (Mann, 1855)